“Kabulok Komad Quartet Card” Learning Media: Student Interest and Learning Outcomes in Science - Sri Wahyuni; Muhammad Hanif; Sudarmiani Sudarmiani (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study examines the effectiveness of the “Kabulok Komad Quartet Card” learning media in improving students’ learning interest and learning outcomes in science (IPAS) learning at the elementary school level. Methodology: A quantitative approach was employed using a quasi-experimental posttest non-equivalent control group design. The participants consisted of 22 fourth-grade students at Elementary School 01 Nambangan Lor, Madiun City, divided into an experimental group (n = 11) that utilized the Kabulok Komad Quartet Card learning media and a control group (n = 11) that used conventional textbook-based learning media. Data were collected using a learning interest questionnaire and a learning outcomes test, then analyzed through descriptive statistics and independent sample t-tests at a 0.05 significance level. Main Findings: The results reveal that students in the experimental group demonstrated significantly higher learning interest and learning outcomes compared to those in the control group. The t-test results indicate a significant difference in learning interest (t = 5.358, p < 0.05) and learning outcomes (t = 5.194, p < 0.05) between the two groups. These findings suggest that the Kabulok Komad Quartet Card learning media is effective in creating an engaging, contextual, and student-centered learning environment. Novelty/Originality of this study: This study provides empirical evidence that integrating local cultural content through game-based learning media can enhance both affective and cognitive aspects of learning in elementary science education.